Intense light unleashes male-male courtship behaviour in wild-type Drosophila. - Ueda, A.; Berg, A.; Khan, T.; Ruzicka, M.; Li, S.; Cramer, E.; Iyengar, A.; Wu, C.F. (Open biology, 2023)
Drosophila courtship studies have elucidated several principles of the neurogenetic organization of complex behaviour. Through an integration across sensory modalities, males perform stereotypic patterns of chasing, courtship song production and copulation attempts. Here we report a serendipitous finding that intense light not only enhances courtship toward female targets but also triggers unexpected courtship behaviours among male flies. Strikingly, in wild-type male-only chambers, we observed extreme behavioural manifestations, such as 'chaining' and 'wheeling', resembling previously reported male-male courtship behaviours in fruitless mutants and in transformants with ectopic mini-white[+] overexpression. This male-male courtship was greatly diminished in a variety of visual system mutants, including disrupted phototransduction (norpA), eliminated eye-colour screening pigments (white), or deletion of the R7 photoreceptor cells (sevenless). However, light-induced courtship was unhampered in wing-cut flies, despite their inability to produce courtship song, a major acoustic signal during courtship. Unexpectedly the olfactory mutants orco and sbl displayed unrestrained male-male courtship. Particularly, orco males attained maximum courtship scores under either dim or intense light conditions. Together, our observations support the notion that the innate male courtship behaviour is restrained by olfactory cues under normal conditions but can be unleashed by strong visual stimulation in Drosophila.